Needs Analysis of Interactive Learning Media Based on Smart Apps Creator for Natural and Social Sciences in Elementary School - Titin Nurkhafifah; Beni Habibi; Sutji Muljani (FKIP - Universitas Riau, 2026)
This study aims to assess the necessity of Smart Apps Creator-based interactive learning media for teachers and students within the context of Natural and Social Sciences instruction in elementary schools. Employing a descriptive research design, this study involved 5 classroom teachers and 25 elementary students from the Watukumpul District, Pemalang Regency, as participants. Primary data were gathered using Likert-scale questionnaires to objectively map the needs profile, followed by quantitative descriptive analysis. Empirical evidence reveals that the urgency of teachers' requirements for interactive learning media falls into the very high category, achieving a mean score of 4.28. Key aspects highlighted by educators included concept visualization, media usability, and efficacy in stimulating student engagement. Correspondingly, student responses reflected a very high level of need, with a mean score of 4.58, specifically emphasizing a preference for interactive quizzes, audiovisual content, and an engaging user interface. The alignment of these findings underscores the critical need for accessible and visually rich media for Natural and Social Sciences subjects. Consequently, developing media utilizing Smart Apps Creator is proposed as a relevant solution to enhance the quality of elementary education.